A Guide to Small-Scale Energy Harvesting Techniques - Manyala, Reccab (IntechOpen, 2020)
The use of energy it is argued started about two million years ago when humans started cooking their food using firewood. As humans developed new skills with increased activities, energy interaction and usage emerged. Energy was used not only for domestic functions but also for space applications. With industrialization, humans realized that energy was needed to move machines and do other things as well. In this quest, and without understanding the consequences of using fossil fuels extensively, many problems arose. Researchers in energy embarked on a journey to study different forms of energy. To understand different needs, researchers have tried to come up with ways in which small-scale energy harvesting can be adapted to different needs that do not require heavy-duty energy production.This book attempts to present a number of ideas regarding a few selected small-scale energy harvesting methods and techniques as well as theories and products that may be helpful in improving the quality of life. Some of the new products are still in the prototype stage, while others are already being utilized. Many researchers in small-scale energy harvesting and those aspiring to follow this path of research will find this book not only motivating but also a useful guide in their endeavors.